Thyroid and renal function in cats following low‐dose radioiodine (111Mbq) therapy. (22nd July 2019) - Finch, N. C.; Stallwood, J.; Tasker, S.; Hibbert, A.
Abstract : Objectives: To describe the effect of low‐dose (111MBq) radioiodine therapy on thyroid and renal function in hyperthyroid cats over a 12‐month follow‐up period. Materials and Methods: Client‐owned hyperthyroid cats underwent low‐dose radioiodine therapy and were followed‐up for 12 months. Immediately before radioiodine treatment, and at 1, 6 and 12 months afterwards, total thyroxine, thyroid stimulating hormone, serum creatinine and glomerular filtration rate were measured. Results: Fifteen of the 24 (63%) cats achieved euthyroidism following low‐dose radioiodine treatment. The incidence of overt hypothyroidism was six of 24 (25%) cats. Of the six cats developing overt hypothyroidism, three had decreased renal function, with decreased glomerular filtration rate preceding azotaemia in two of these individuals. Transient overt or subclinical hypothyroidism before restoration of euthyroidism was not observed. Clinical Significance: Low‐dose radioiodine is effective treatment for hyperthyroidism in most cats but overt hypothyroidism may develop in some. Concurrent early decline in renal function may only be detected by measuring glomerular filtration rate rather than serum creatinine in some cats. Monitoring following radioiodine treatment should include total thyroxine and thyroid stimulating hormone and measurement of glomerular filtration rate should be considered in non‐azotaemic cats.